The Use of Demonstration Model Assisted by Audio-Visual Media to Improve Learning Outcomes in Rhythmic Gymnastic Material - Wildan Aulya Rochman; Dini Rosdiani; Yudi Hidayat (Journal of Physical and Outdoor Education, 2026)
The purpose of this study was to determine and examine whether the use of demonstration models assisted by audio-visual media can improve learning outcomes rather than using conventional models. The method in this research is quasi experiment with pretest-posttest control group design model. Based on the results of data analysis, it shows that the learning outcomes of rhythmic gymnastics of experimental classes with demonstration models assisted by audio-visual media in the form of learning videos obtained an average value of 81.35 with the highest value of 94 and the lowest value of 63, while the control class using conventional demonstration models has an average value of 67.55 with the highest value of 81 and the lowest value of 50. So it can be concluded that the use of demonstration models assisted by audio-visual media significantly improves rhythmic gymnastics learning outcomes compared to conventional demonstration model learning models in class V students of Citeureup Mandiri 1 State Elementary School.